Living Aswaja as a Model Strengthening Anti-Radicalism Education at INISMA Jambi - Saidina Usman; Sayed; Uswatun Hasanah (Yayasan Zia Salsabila, 2025)
Ahlussunnah wal Jama'ah (Aswaja) is a way of thinking and doing that is deeply rooted in the Islamic tradition of the Indonesian archipelago. At the Muaro Jambi Islamic Institute (INISMA), Aswaja values are one of the pillars of student character formation. This study aims to analyze (1) How the concept of Living Aswaja is understood and internalized within the Muaro Jambi Islamic Institute (INISMA) environment (2) What is the impact of the implementation of Living Aswaja on the attitude of religious tolerance of INISMA Jambi students. This type of research is qualitative with a focus on field research. (1) The concept of Living Aswaja within the Muaro Jambi Islamic Institute (INISMA) is understood as an effort to revive the values of Ahlussunnah wal Jama'ah an-Nahdliyah in the academic, social, and spiritual life of the academic community. This understanding does not only stop at the theoretical level, but also extends to daily practice, both in the teaching and learning process, social interactions, and student activities. Living Aswaja at INISMA is present as an ideological identity as well as an institutional culture that shapes the mindset and behavior of its citizens. (2) This study found that the implementation of Living Aswaja at INISMA Jambi has a significant influence on the formation of religious tolerance attitudes among students. This phenomenon indicates that the principle of tawassuth (moderation) has been brought to life in their interactions.